CHANGE OF FAMILY PARADIGM: THE SUPERIOR INTEREST OF THE BOYS AND THE GIRLS TO HAVE A FAMILY FOUNDED BASED ON AFFECTIVE LINKS AND TO HIS RIGHT TO BE HEARD. (Perspectivas de las Ciencias Económicas y Jurídicas, 2017)
The present work has aimed to identify the transformations that the family has experienced as a natural and fundamental element of the society, as a result of its adaptation to the socio-cultural context in which it develops.An influential factor of this paradigmatic change, subject under analysis in the present article, was the recognition of children as subjects of concrete rights, legally excercised after the sanction of the Convention on the Rights of the Child.This Convention is imperative for those States that have ratified it and are required to reflect it in their national systems of promotion and protection, to guarantee the right of children and adolescents to be raised in a family and community environment, without being subject of any interference and discrimination by the family model that has given him an adequate care.
Keywords: child rights; family; protection systems